2001
DOI: 10.1021/jf0100393
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Total, Neutral, and Phospholipids in Mapará (Hypophthalmus sp.) from the Brazilian Amazonian Area

Abstract: Ten lots of mapará (Hypophthalmus sp.), captured from the Amazon River, Brazil, were analyzed for their lipid content and fatty acid composition. This knowledge would allow for the development of adequate processing methods and the formulation of therapeutic diets. Separation into neutral and phospholipids was accomplished by silica-gel column chromatography. Fat from the muscular tissue and from the orbital cavity of the mapará was analyzed by high-resolution gas chromatography-mass spectrometry in two differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 14 publications
2
22
1
1
Order By: Relevance
“…The major fatty acids identified in the S. triostegus were palmitic acid, stearic acid, oleic acid, linoleic acid, AA, EPA, DPA and DHA acid in all seasons. Similar results for other fish species have also been reported in the literature (Maia et al, 1995;Inhamuns and Franco, 2001;Almeida et al, 2008).…”
Section: Fatty Acid Composition Of Phospholipidsupporting
confidence: 91%
See 1 more Smart Citation
“…The major fatty acids identified in the S. triostegus were palmitic acid, stearic acid, oleic acid, linoleic acid, AA, EPA, DPA and DHA acid in all seasons. Similar results for other fish species have also been reported in the literature (Maia et al, 1995;Inhamuns and Franco, 2001;Almeida et al, 2008).…”
Section: Fatty Acid Composition Of Phospholipidsupporting
confidence: 91%
“…In S. triostegus, the level of DHA was lowest in summer whereas DHA was very high in winter. Inhamuns and Franco (2001) has reported that in the phospholipids there is a high level of polyunsaturated fatty acids, including primarily DHA, AA, linolenic acid, and EPA. Farkas (1984) has noted that one of the main changes at the level of fatty acid composition is an increase in DHA at low temperatures.…”
Section: Fatty Acid Composition Of Phospholipidmentioning
confidence: 99%
“…(0.66-0.98) (Inhamuns et al, 2009), C. macropomum (0.41) (Almeida et al, 2008) and Hypophthalmus sp. (1.5-1.6) (Inhamuns & Franco, 2001). In those fish, all the n-3/n-6 ratios were affected by the high proportion of DHA in their muscles.…”
Section: Resultsmentioning
confidence: 91%
“…in dry season (Inhamuns et al, 2009); mapará (Hypophthalmus sp.) (Inhamuns & Franco, 2001); and spotted sorubim (Pseudoplatystoma corruscans) (Tanamati et al, 2009); as well as in wild freshwater fish from other regions (Jabeen & Chaudhry, 2011 (Jabeen & Chaudhry, 2011). All the quantified Pufa showed quite similar values in both dorsal and ventral muscles of wild A. gigas, except for linoleic acid, which was higher than the other Pufa and is considered one of the essential fatty acids for freshwater fish (NRC, 2011).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation